A Retrospective Study of Postmastectomy Pain Syndrome: Incidence, Characteristics, Risk Factors, and Influence on Quality of Life - Yang Meijuan; Peng Zhiyou; Tang Yuwen; Feng Ying; Chen Xinzhong (The Scientific World Journal)
Objective. The underlying cause for postmastectomy pain syndrome (PMPS) and its impact on quality of life remain unclear. The objective of this study aims to determine retrospectively the prevalence of PMPS, its predicting risk factors, and its impact on quality of life. Method. In this survey, 225 women completed a battery of questionnaires. The questionnaires comprised the short form of the McGill Pain Questionnaire (SF-MPQ) exploring the characteristics and the description of the pain, and a Short Form-36 (SF-36) Health Survey evaluating quality of life. Logistic regression analyses were subsequently performed to identify risk factors for PMPS. Results. 62 women (27.6%) reported PMPS as a consequence of surgery, and the pain was generally mild, mostly localized in breast area and intermittent. The pain was mainly described as aching (62.9%). 144 women reported sensory disturbance. We found that only the younger age is the predictive factor for PMPS (P<0.05). Compared to the patients who did not experience PMPS, those who suffered from PMPS had significantly worse scores in role limitations due to physical problems (role physical, RP), body pain (BP), general health (GH), vitality (VT), role limitations due to emotional problems (role emotional, RE), and mental health (MH) (P<0.05). Conclusion. PMPS is a significant problem, and the possible risk factors should be further explored. Patients with PMPS have significant worse quality of life, suggesting that patients should be well informed about the likelihood of experiencing the pain, and they may be afforded greater predictability and higher perceived control to enhance their quality of life.